A Novel Approach for a Functional Group to Predict Protein in Undigested Residue and Protein Digestibility by Mid-Infrared Spectroscopy. Issue 11 (November 2013) - Wang, Li Fang; Swift, Mary Lou; Zijlstra, Ruurd T.
To evaluate nutrient digestibility, we propose the novel approach of functional group digestibility (FGD). The FGD was based on the absorbance of specific Fourier transform infrared (FT-IR) peaks and the ratio of an inorganic indigestible marker in diet and digesta, without calibration. For application, samples of diet and digesta of wheat with predetermined crude protein (CP) digestibility were scanned on an FT-IR spectrometer equipped with a single-reflection attenuated total reflection (ATR) attachment. The FGD in the amide I region (1689–1631 cm −1 ) of digesta spectra was strongly related ( R 2 = 0.99) with CP digestibility. The measured diet CP digestibility ranged from 60.4 to 87.8% with a standard error of prediction of 1.09%. In conclusion, instead of predictions based on calibrations, FGD can be calculated directly from spectra, provided the ratio of marker in diet and undigested residue is known, and then accurately predicts nutrient digestibility.